Evaluasi Program Pendidikan dalam Meningkatkan Prestasi Akademik Siswa Disekolah SMP Negeri 1 Hamparan Perak - Almaajid, Rizqi; Aidin, Winda; Sholehah, Dini; Pradita, Syakila; Arifandi, Ridwansyah; Mayasari, Indah; Ayumi, Malikah; Nasution, Inom (LPPPI Publishing, 2024)
Improving student academic achievement is one of the main priorities in the world of education. SMP Negeri 1 Hamparan Perak has implemented various educational programs in an effort to achieve this goal, such as tutoring programs, improving learning facilities, and teacher training. This research aims to activate the effectiveness of educational programs that have been implemented at SMP Negeri 1 Hamparan Perak in improving students' academic achievement. The evaluation was carried out using mixed methods, namely a combination of a quantitative approach through analysis of student academic achievement data and a qualitative approach through interviews with related parties. The evaluation results show that the tutoring program has had a positive impact on improving student academic achievement, however the program to improve learning facilities and teacher training has not been fully effective. Based on these findings, this research provides recommendations for optimizing the implementation of educational programs by integrating digital technology, increasing parental involvement, and conducting regular teacher training. With continuous evaluation and improvement, it is hoped that student academic achievement at SMP Negeri 1 Hamparan Perak can continue to improve significantly.